SPIRIT IN THE CRYPT NEGARESTANI VS LAND. - Le, Vincent (Cosmos & History, 2019)
Iranian philosopher Reza Negarestani's first 2008 book Cyclonopedia was written under the influence of Nick Land's nihilistic and antihumanist philosophy which seeks to critique anthropomorphism by confronting us with our coming extinction beyond which our concepts of reason cannot reach. Since Cyclonopedia's publication, however, Negarestani has left behind Landian nihilism to develop in his 2018 book Intelligence and Spirit a neorationalist philosophy of mind whose primary influences are Sellars, Brandom, and Hegel. At 579 clearly written yet dense pages, it is difficult even for a review article to encapsulate the book in its entirety. The first half of this article instead aims to provide a sense of the book's overall project by focusing on how Negarestani outlines and develops his neorationalist philosophy through a critique of Land's antihumanism. Never one to remain silent whilst others seek to resurrect Hegel from the dead, since December 2018, Land has been releasing a draft on his blog Urban Futures 2.1 of his new monograph Crypto- Current: Bitcoin and Philosophy, which proffers the most up to date articulation of his main antihumanist tenets. Having organized Intelligence and Spirit around Negarestani's objections to Land, this article's second half turns to Crypto-Current to see how Land is able to provide convincing responses to each of Negarestani's objections, showing some to be based on strawman characterizations, others to stem from misunderstandings of Land's position, and still others to lack traction at all. By putting Negarestani and Land's new books in combat, we will ultimately see that the grounds for Negarestani's efforts to move continental philosophy from its Kanto-Landian phase to a renewed Hegelian phase is unsuccessful in that antihumanism is able to respond to each of his objections in kind.